(untitled) (Advanced Research & Development Journal, 2025)
The bidirectional isolated full-bridge converter (BIFBC) is extensively utilized in energy storage systems, electric vehicles, and renewable energy interfaces because to its capability to transfer power in both directions while maintaining galvanic isolation. However, typical converters experience significant switching losses, electromagnetic interference, and component stress due to hard-switching, particularly at elevated switching frequencies. This paper examines the utilization of active and inactive snubber circuits to facilitate softswitching in BIFBC topologies, hence addressing these issues. Passive snubbers consist of capacitors and inductors. Their resonance components modify the converter’s operation, facilitate energy recovery, and reduce voltage stress. Active snubbers enhance the softswitching range and improve system efficiency across diverse load circumstances by recovering all energy dissipated through regulated switches. The study examines the impact of many factors, including design characteristics, switching transitions, and loss mitigation measures, on the overall performance of the converter. Passive snubbers remain attractive for straightforward and cost-effective designs. Simulations and comparative analyses indicate that active snubbers perform more effectively and induce reduced switching stress. To optimize soft-switching techniques in contemporary bidirectional isolated full-bridge converters, the findings illustrate the trade-offs among dynamic performance, efficiency, and complexity.